The epigenetic regulatory network of long noncoding RNAs in hepatocellular carcinoma - Zhaoqi Shi; Shengxi Jin; Xiaolong Liu; Mengting Jiang; Yifeng Fang; Parikshit Asutosh Khadaroo; Hui Lin; Xiaoxiao Fan (Genes and Diseases, 2025)
Long noncoding RNAs (lncRNAs) are endogenous noncoding RNAs exceeding 200 bases in length that are prevalent in malignant tumors and are closely associated with the onset and progression of hepatocellular carcinoma. The synthesis of lncRNAs exhibits similarities to that of protein-coding transcripts, which is regulated by epigenetic modifications. Recent research has highlighted the significant regulatory role of epigenetic modifications in the transcription of lncRNA genes in hepatocellular carcinoma. This review outlines the impact of epigenetic modifications, including DNA methylation, histone modification (methylation and acetylation), RNA modification, and microRNAs on the transcription of lncRNA genes in hepatocellular carcinoma and delves into the underlying mechanisms by summarizing how these lncRNA genes contribute to the development and progression of hepatocellular carcinoma.